Organizational Culture's Influence on Employee Performance Through Job Satisfaction - Umasangadji, Abdi Soleman; Rajak, Adnan; Kamis, Ruslan A.; Arilaha, Muhammad Asril (AIBPM Publisher, 2022)
This study examineS the influence of organizational culture on performance through job satisfaction. The population in this study was the overall employees who worked in the Ternate City Local Government. The total research sample was 103 respondents who worked at the Department of Industry and Trade (Disperindag) of Ternate City. Validity and reliability tests are used as part of instrument testing. This study used hierarchical regression analysis using statistical package for social scientists (SPSS) as a statistical test tool for hypothesis testing. The results showed that job satisfaction mediates the relationship between organizational culture and performance at the Ternate City Industry and Trade Office (Disperindag).Keywords: Organizational Culture, Performance, Job Satisfaction